2021
DOI: 10.1101/2021.10.25.465747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural age-related sleep-wake alterations onset prematurely in the Tg2576 mouse model of Alzheimer’s disease

Abstract: Sleep insufficiency or decreased quality have been associated with Alzheimer disease (AD) already in its preclinical stages. Whether such traits are also present in rodent models of the disease has been poorly addressed, somewhat disabling the preclinical exploration of sleep-based therapeutic interventions for AD. We investigated age-dependent sleep-wake phenotype of a widely used mouse model of AD, the Tg2576 line. We implanted electroencephalography/electromyography headpieces into 6 months old (plaque-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…These sleep symptoms can manifest years before cognitive decline, and alterations in sleep can influence the deposition rates of Aymloid-β (Aβ) plaques that are the hallmark of AD, contributing to disease risk [2][3][4] . Consistent with this, some transgenic AD mouse models that overproduce Aβ display sleep disruptions prior to plaque formation, even without evident neuronal loss [5][6][7][8][9][10][11] . Recently, human studies have found that harbouring a high genetic risk for AD correlates with sleep changes, such as increased sleep rebound following sleep loss, even in young adults 12 .…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…These sleep symptoms can manifest years before cognitive decline, and alterations in sleep can influence the deposition rates of Aymloid-β (Aβ) plaques that are the hallmark of AD, contributing to disease risk [2][3][4] . Consistent with this, some transgenic AD mouse models that overproduce Aβ display sleep disruptions prior to plaque formation, even without evident neuronal loss [5][6][7][8][9][10][11] . Recently, human studies have found that harbouring a high genetic risk for AD correlates with sleep changes, such as increased sleep rebound following sleep loss, even in young adults 12 .…”
Section: Introductionsupporting
confidence: 54%
“…Much less clear in this formulation is how the sleep and wake-dependent accumulation of Aβ in turn disrupts sleep, but AD-related cell death of critical sleep/wake regulatory neurons has been proposed as a possible mechanism (Fronczek et al, 2012; Lim et al, 2014; Manaye et al, 2013). However, sleep symptoms in AD patients often appear before cognitive impairment (Sterniczuk et al, 2013), and at least some transgenic AD mouse models show disrupted sleep phenotypes preceding plaque burden (Huitron-Resendiz et al, 2002; Jyoti et al, 2010; Kollarik et al, 2021; Platt et al, 2011; Roh et al, 2012; Sterniczuk et al, 2010; Wang et al, 2002), even in the absence of neuronal loss (Colby-Milley et al, 2015; Irizarry et al, 1997; Sethi et al, 2015). An alternative hypothesis is that Aβ itself acts as a signalling molecule to modulate sleep and that this normal sleep regulatory process is disrupted in AD progression by changes in Aβ oligomeric state or plaque formation.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 Consistent with this, some transgenic AD mouse models that overproduce Aβ display sleep disruptions prior to plaque formation, even without evident neuronal loss. 5 , 6 , 7 , 8 , 9 , 10 , 11 Recently, human studies have found that harboring a high genetic risk for AD correlates with sleep changes, such as increased sleep rebound following sleep loss, even in young adults. 12 These observations suggest that there may be underlying early biological processes important for sleep regulation that are governed by AD susceptibility genes and contribute to disease progression.…”
Section: Introductionmentioning
confidence: 99%